2018
DOI: 10.1002/mrc.4806
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing signal‐to‐noise ratio and resolution in low‐field NMR relaxation measurements using post‐acquisition digital filters

Abstract: The traditional way to enhance signal‐to‐noise ratio (SNR) of nuclear magnetic resonance (NMR) signals is to increase the number of scans. However, this procedure increases the measuring time that can be prohibitive for some applications. Therefore, we have tested the use of several post‐acquisition digital filters to enhance SNR up to one order of magnitude in time domain NMR (TD‐NMR) relaxation measurements. The procedures were studied using continuous wave free precession (CWFP‐T1) signals, acquired with ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…Although the SNR of CWFP-T1 is much lower than obtained with IR, the T1 values were similar. We demonstrated that several post-acquisition digital filters (low pass, linear and logarithm compression, Savitzky-Golay, and Wavelet filters) can be used to enhance SNR in CWFP-T1 signals without significant deviation of the T1 values [39]. Figure 11 shows a SNR enhancement of one order of magnitude on CWFP-T1 signal using second-order, a 41-points window, and a Savistiky-Golay (SG) filter.…”
Section: Fast and Simultaneous T 1 And T 2 Measurementsmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the SNR of CWFP-T1 is much lower than obtained with IR, the T1 values were similar. We demonstrated that several post-acquisition digital filters (low pass, linear and logarithm compression, Savitzky-Golay, and Wavelet filters) can be used to enhance SNR in CWFP-T1 signals without significant deviation of the T1 values [39]. Figure 11 shows a SNR enhancement of one order of magnitude on CWFP-T1 signal using second-order, a 41-points window, and a Savistiky-Golay (SG) filter.…”
Section: Fast and Simultaneous T 1 And T 2 Measurementsmentioning
confidence: 96%
“…Therefore, samples with higher fat contents show a large 100 ms peak. The ratio of the area of these two peaks has been used to measure fat content in beef with higher precision than standard CWFP sequences [39].…”
Section: Agri-food Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low SNR in the CWFP–T 1 signal is due to the small flip angles in the pulse sequence. However, the SNR of the CWFP–T 1 signals can be enhanced using post-acquisition digital filters, such as Savistky–Golay or wavelet filters [ 36 ]. Figure 10 shows that the CWFP–T 1 signal has similar results to those obtained with the standard IR method; however, in a shorter measuring time [ 14 ].…”
Section: One-dimensional (1d) Pulse Sequencesmentioning
confidence: 99%
“…Fonte: figura adaptada da referência71 .Com permissão de John Wiley and Sons. Contudo, após a aquisição os sinais obtidos com as sequências de pulsos CPMG e Discussão utilizando uma solução contendo o complexo [Mn(H 2 O) 6 ] 2+ 0,02 mM, cujo T 2 = 680 ms (Figura 29 (a) -sinal vermelho -escala de tempo superior).…”
unclassified